Questioning the Decline in the Number of Hand Catching Operation by the Corruption Eradication Commission - Putriyana, Ayu; Muthia, Arini Azka (Kertha Patrika, 2026)
One way the Indonesian government eradicates corruption is by forming the Corruption Eradication Committee and one way to take action against corruption is by conducting hand catching operation. The purpose of writing this article is to explain the causes of the decline in the number of hand catching operation in recent years, especially in 2024, even though the Corruption Eradication Committee hand catching operation had been intensively carried out to prosecute corruption, but instead of experiencing a spike, the number of hand catching operations actually decreased. The preparation of this article uses a normative legal research method related to hand catching operations and the latest Corruption Eradication Committee Law. In addition, in order for the analysis results to be more in-depth, the author also uses a legislative and conceptual study approach. There are 2 (two) research results in this article, namely, first, the term hand catching operations is indeed not found in the Criminal Procedure Code and the Corruption Eradication Committee Law, but a series of actions that are the same as hand catching operation containing the stages of wiretapping, searches, arrests and confiscations have been regulated in the latest Corruption Eradication Committee Law. Second, the hand catching operation which is currently experiencing a decline in 2024 is due to several things such as changes in the hand catching operation mechanism in carrying out wiretapping, searches, and/or confiscations, permission from the Supervisory Board is required. Hand catching operation has also been studied by corruptors who on average have high intellectual education so that by studying the hand catching operation method